2008
DOI: 10.1021/jp076718j
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Hydrogen Interaction and Saturation on Small Titanium Clusters

Abstract: This work explores the nature of interaction and saturation of hydrogen molecules on small titanium clusters using ab initio calculations. Molecular dynamics simulations and ensuing charge density maps were used to gain insight into the key steps involved in dissociation of the hydrogen molecule on the metal clusters. The mechanistic insights gleaned from these simulations were subsequently utilized to obtain realistic models of the hydrogen saturated titanium clusters. It was found that the most stable hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 75 publications
(111 reference statements)
3
24
0
Order By: Relevance
“…Full geometry optimizations were followed by an evaluation of the vibrational frequencies and the Raman activities. In a recent study carried out by one of us on titanium containing complexes, it was shown that calculations using this method yield geometries and vibrational frequencies in good agreement with experiment [25]. It was also shown in an earlier study that the B3LYP/6-31G* vibrational frequencies, scaled by a factor of 0.9614, yield values in close agreement with experiment [26].…”
Section: Computational Detailssupporting
confidence: 53%
“…Full geometry optimizations were followed by an evaluation of the vibrational frequencies and the Raman activities. In a recent study carried out by one of us on titanium containing complexes, it was shown that calculations using this method yield geometries and vibrational frequencies in good agreement with experiment [25]. It was also shown in an earlier study that the B3LYP/6-31G* vibrational frequencies, scaled by a factor of 0.9614, yield values in close agreement with experiment [26].…”
Section: Computational Detailssupporting
confidence: 53%
“…59,[61][62][63][64][65][66][67][68][69] This level of theory has been found to yield reliable geometries and vibrational frequencies for a number of first-row transition metal systems. [70][71][72][73][74] Nonetheless, in light of recent studies indicating the improved performance of the BP86 and TPSS functionals in describing transition metal containing systems, the geometries and energies of 2 were also calculated using these functionals and the larger TZVPP basis sets. [75][76][77] These results are shown in Table S4 which indicate that the B3LYP/6-31G* level of theory is reliable for the systems investigated in this study.…”
Section: Methodsmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41][42][43][44][45] Recent studies have indicated that small icosahedral titanium clusters form stable hydrogen-saturated complexes. [46][47][48] In this paper we investigate icosahedral and cuboctahedral clusters of Sc, Ti, and Zr and examine if this is a general phenomenon exhibited by neighboring elements of titanium from the same row or group. In the absence of any experimental and theoretical studies of hydrogen adsorption and saturation on these metal clusters, we compare and contrast our findings with the more widely studied aluminum clusters.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Electronic structures of isolated and hydrogen-loaded titanium clusters have been the topic of a number of recent investigations. [46][47][48][49][50][51] To the best of our knowledge, effects of hydrogen adsorption and saturation have not been investigated for zirconium or scandium clusters. However, electronic structures of isolated zirconium and scandium clusters have been the focus of some recent theoretical studies.…”
Section: Introductionmentioning
confidence: 99%